2017
DOI: 10.5812/ijem.43319
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Types of Statins on Lipid Profile: A Perspective on Asians

Abstract: ContextThe present review aimed at reviewing the effects of different statins on lipid profile, particularly in Asians.Evidence AcquisitionPubMed searches were conducted using the keywords ‘statin, effect, and lipid profile’ from database inception through March 2016. In this review, 718 articles were retrieved from the primary search. After reviewing the titles, abstracts, and full texts, we found that 59 studies met our inclusion criteria. These also included subsequent reference searches of retrieved articl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 52 publications
0
20
1
2
Order By: Relevance
“…At the end of 12 weeks, target values were achieved with rosuvastatin in 76% of patients, with atorvastatin in 58%, and with simvastatin in 53%. 16 It is known that atorvastatin 20 mg is pharmacokinetically the same as rosuvastatin 10 mg. 17 In the present study, LDL cholesterol level decreased with both statins at the end of the 12th month versus baseline, but no statistically significant difference was found between the groups.…”
Section: Discussioncontrasting
confidence: 62%
“…At the end of 12 weeks, target values were achieved with rosuvastatin in 76% of patients, with atorvastatin in 58%, and with simvastatin in 53%. 16 It is known that atorvastatin 20 mg is pharmacokinetically the same as rosuvastatin 10 mg. 17 In the present study, LDL cholesterol level decreased with both statins at the end of the 12th month versus baseline, but no statistically significant difference was found between the groups.…”
Section: Discussioncontrasting
confidence: 62%
“…A counterpoint to this argument would be that the subjects in our STEMI population were more likely to be on oral medications for hyperlipidemia, and it is known that statins exert a pleiotropic anti-inflammatory effect 33 . Statins result in lower TC, LDL-C and TG levels 34 . A study demonstrated the effect of statins on outcome modification in patients with low LDL-C levels.…”
Section: Discussionmentioning
confidence: 99%
“…These are among the most commonly prescribed medicines worldwide for the prevention of cardiovascular complications and mortality, and studies have suggested that, in addition to decreasing serum lipids, statins also show pleiotropic effects that are not directly associated with cholesterol synthesis, such as improving endothelial dysfunction, reducing inflammatory response, stabilizing atherosclerotic plaque, and decreasing thrombogenic response . Compared with hydrophilic statins (eg, pravastatin), lipophilic statins (egatorvastatin and simvastatin) can be more widely distributed to the tissues and cells through passive diffusion …”
Section: Introductionmentioning
confidence: 99%